Pengendalian Mutu Kopi Luwak pada Perusahaan CV Sari Alam Pegunungan di Kabupaten Bangli - KEMIT, NIKODEMUS; SUAMBA, I KETUT; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.3, Juli 2016, 2016)
Quality Control of Luwak Coffee at CV Sari Alam PegununganCompany in Kabupaten Bangli Quality is a dynamic condition related to products, services, people, processes, andenvironments that meet or exceed expectations. Quality control is the measurementof the performance of the product, compared with the standards and specificationsof the product, and perform corrective action if any irregularities. This researchaims to determine the processing of luwak coffee, implementation of qualitycontrol, and optimization of the total cost of the quality control in CV Sari AlamPegunungan Bangli. The location of this research is selected by purposivesampling. Data used in this study is qualitative and quantitative data, the dataobtained and analyzed. The results showed that the processing is done through eightstages and implement quality control. CV Sari Alam Pegunungan conducts qualitycontrol from raw material to final product. The comparison of the total quality costoptimum (TQC *) to a total quality cost actual (TQC) shows that the costs incurredby the quality of the company is efficient / optimal. It can be seen from thedifference between the calculation of the extent of damage and the total cost for thequality of the company by the optimum relatively small and well-tolerated, with thedifference between the total cost for the quality (TQC) Rp. 65 081 and thedifference in the level of damage civet coffee by 26 Kgs. As for the values of theproportion of the damage occurred in the company's products are still withintolerable limits map control / control. This shows that the quality controlundertaken by CV Sari Alam Pegunungan has been running well.
Keywords: quality, quality control, luwak cofee, quality cost